Thoracic changes and exercise capacity in patients with adolescent idiopathic scoliosis - Bruna Marques de Almeida Saraiva; Thamiê Cristina Stella; Geferson da Silva Araujo; Evandro Fornias Sperandio; Victor Zuniga Dourado; Milena Carlos Vidotto
Abstract Introduction: The spine deformity due to adolescent idiopathic scoliosis (AIS) generates respiratory mechanical limitations that may reduce the physical activity performance. Objective: To evaluate the thoracic deformity, exercise capacity and lung function in AIS patients comparing to healthy adolescentes. Besides investigating associations between thoracic deformity and exercise capacity in AIS patients. Methods: Thirty-two AIS patients and 22 healthy adolescents underwent chest wall evaluation by photogrammetry. We created thoracic markers shaped as angles (A): A3 (xiphoid process and the last false rib on the right and left sides) and A5E (inframamilar / inferior angle of the scapula / left acromion). Individuals were submitted to incremental shuttle walk test (ISWT) and physiological responses were quantified: oxygen consumption (VO2), tidal volume (VT), minute ventilation (VE), the rate of gas exchange (R) and the walked distance (ISWD). Pulmonary function test was performed and the forced vital capacity (FVC) and expiratory volume in first second (FEV1) were obtained. Results: Patients with AIS presented FVC (p = 0.015), FEV1 (p = 0.044), VO2 (p = 0.015), VO2/kg (p = 0.008), VT (p < 0.001), VE (p = 0,010) and ISWD significantly reduced compared to healthy adolescents. We found moderate correlations between the thoracic markers A5E and VO2 (r = -0.480, p = 0.001), A3 and VE/VO2 (r = -0.480; p = 0.001) and R (r = -0.480, p = 0.001) in AIS patients. Conclusion: Patients with AIS presented reduced exercise capacity and reduced pulmonary function. The thoracic deformity is related to worse exercise capacity in individuals with AIS.